Effect of Plant Growth Promoting Rhizobacteria (PGPR) in Inhabiting the Growth of Fusarium oxysporum in vitro (Latakia University Journal -Biological Sciences Series, 2024)
This experiment aimed to study the effect of six species of plant growth promoting rhizobacteria(BGPR) (Frateuria aurantia, Pseudomonas fluorescens, Rhizobium leguminosarum, Bacillus cerculans, Bacillus megaterium, Azotobacter chroococcum) Invitro.     Studied directly using the double cultivation method on a PDA environment in the same dish for the fungus and bacteria, to study the effect of secreted substances in the environment, and indirectly to study the effect of volatile substances in inhibiting the growth of the fungus by cultivation in the closed dish using two dishes. The mushrooms were grown on a PDA medium, and the bacteria on a YEMA medium. After incubating the dishes for 5-7 days, the diameter of the fungal colony was measured and the percentage of fungal growth inhibition compared to the control was calculated.     The results showed that all bacterial species inhibited the growth of Fusarium oxysporum as a result of its secretions and the volatile substances it secreted, with Bacillus cerculans significantly superior to the rest of the bacterial species, as the diameter of the pathogenic fungus colony in treatment (F+Bc) was 0.8 cm and 3.76 cm compared with the control (F) 8 cm and 4.8 cm. and the percentage inhibition was 90% and 31.25%, respectively. The results indicate the ability of PGPR bacteria used to inhibit the growth of the pathogenic fungus Fusarium oxysporum and the possibility of using them in biological control.